Islamic Counseling Guidance Mujadalah Technique for Child Victims of Psychological Violence - Majdi, M. Zuhdi Zainul; Suryadi, Iwan Eka; Hadi, Syamsul (Scidacplus, 2024)
Violence is an act committed by someone or a number of people who are in a strong position (feel strong) to someone or some people who are in a weak position (seen as weak/weakened), both physically and non-physically. The purpose of the study is how the Islamic counseling guidance mujadalah technique is effective in increasing understanding and awareness of child victims of psychological violence. Research using qualitative with case study method. The subjects used in the study were client